2019
DOI: 10.1103/physrevb.100.104408
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of electronic, magnetic, and structural properties of GdB6 from first principles

Abstract: Gadolinium hexaboride (GdB 6 ) is a well known field emitter material that has been investigated for more than three decades. We perform a systematical density-functional theory (DFT) study of GdB 6 by using the generalized-gradient approximation and considering the electron interaction parameter U. The basic structural and electronic properties are carefully revised, as well as a strong U-value dependence in determining the antiferromagnetic (AFM) magnetic structures of Gd 4f electronic states. We found a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…At the same time, the arrangement of pairs in each structure is clearly defined, as evidenced by the small width of the resonance line, and also slightly different from each other. Note, that the magnetic structure one of two lowest states E-AFM is consistent with neutron experiment results 27 , 28 , 60 . The absence of the satellites of the second structure may be caused by small volume of the corresponding domain as well as the complexity of the neutron experiment in GdB 6 27 , 28 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…At the same time, the arrangement of pairs in each structure is clearly defined, as evidenced by the small width of the resonance line, and also slightly different from each other. Note, that the magnetic structure one of two lowest states E-AFM is consistent with neutron experiment results 27 , 28 , 60 . The absence of the satellites of the second structure may be caused by small volume of the corresponding domain as well as the complexity of the neutron experiment in GdB 6 27 , 28 .…”
Section: Resultssupporting
confidence: 88%
“…It turns out that two types of magnetic orders, E-AFM and C-AFM (illustrated in Fig. 6 ), lay energetically close to each other in the wide range of the Coulomb repulsion parameter U with energy difference 0.6–1 meV (6–12 K) between them 60 . In its turn, the hysteretic properties of ESR absorption suggest the coexistence in AFM2 phase of domains with different types of magnetic structure.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The calculations with different spin values reveal the +3 charge state of Gd, with spin polarization pointing to magnetism in GdB 6 as per reported results. [ 11,35 ] We found that orbital polarization of GdB 6 is negligible compared to the spin polarization of 4 f orbitals from Gd atom.…”
Section: Resultsmentioning
confidence: 93%
“…[ 3 ] A first‐principles study and experimental analyses have shown evidence of antiferroquadrupolar ordering and crystal field splitting at band structure of CeB 6 . [ 3 ] Similarly, GdB 6 , [ 11 ] NdB 6 , [ 12,13 ] and PrB 6 [ 12 ] exhibited ferromagnetic ordering at low temperatures. [ 14 ] Semiconducting ferromagnetic ordering is observed at low temperatures in the semimetal EuB 6 and paramagnetic Fermi surfaces of PrB 6 , with antiferromagnetic ordering at low temperatures.…”
Section: Introductionmentioning
confidence: 99%